A Compound Cantilevered Plate Model of the Palate-Uvula System during Snoring - Cisonni, Julien; Elliott, Novak; Lucey, Anthony; Heil, M. (RMIT University, 2014)
Flow-induced vibration of the soft tissues of the upper airway is at the origin of snoring noise. For most habitual snorers, the passive motion of the soft palate and its conic projection, the uvula, located at the back of the roof of the mouth, is the main cause of the sleep-related breathing disorder. The flow-induced oscillations of the uvulopalatal system may be modelled using a compound cantilevered flexible plate in a mean channel flow. A parametric study characterises the influence of the mechanical properties of the soft palate and uvula, as well as their relative length, on the flutter-type aeroelastic instability of the plate motion. Results confirm that longer uvulae with typical anatomi- cal properties tend to increase the instability of the FSI system. Further, they show that only much heavier and stiffer uvulae can stabilise the uvulopalatal system and suggest that the tissue properties have to be altered considerably on a large portion of the soft palate to prevent snoring.